Total organic carbon and its role in oxygen utilization in the eastern Arabian Sea. (February 2021) - Shetye, Suhas S.; Kurian, Siby; Vidya, P.J.; Gauns, Mangesh; Shenoy, Damodar M.; Aparna, S.G.; Nandakumar, K.; Karapurkar, Supriya G.
Abstract: We report seasonal and temporal variation of total organic carbon (TOC) in the eastern Arabian Sea (AS). In comparison to the deep, TOC in the top 100 m showed spatial variation with higher concentrations towards northern AS during North east monsoon (NEM) and South west monsoon (SWM). A comparison with the US-JGOFS data (1995) shows warmer temperatures, enhanced TOC and low chlorophyll in the recent years. High TOC is associated with Arabian Sea high saline waters (ASHSW), advected from the Arabian Gulf, might have resulted in an enhancement of TOC in the eastern AS. This excess TOC supports a high abundance of bacteria despite the low primary productivity. TOC oxidation accounted for 14.3% and 22.5% of oxygen consumption for waters with potential density between 24.5 and 27.3 kg/m 3 . This study attains great significance considering the missing links with respect to the role of transport processes in ocean deoxygenation under ongoing warming scenarios. Highlights: First seasonal study on TOC since JGOFS 1995 High TOC concentrations as compared to JGOFS related to Arabian Sea High Saline Water High bacterial counts as compared to JGOFS despite low productivity, highlighting the external source of carbon This study highlights role of transport processes in ocean deoxygenation.